2018
DOI: 10.21037/qims.2018.04.08
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative parameters of intravoxel incoherent motion diffusion weighted imaging (IVIM-DWI): potential application in predicting pathological grades of pancreatic ductal adenocarcinoma

Abstract: D and ƒ derived from IVIM-DWI model can be used to distinguish well/moderately differentiated PDAC from poorly differentiated PDAC. And to serve this purpose, D and ƒ have high diagnostic performance. IVIM-DWI is a promising and non-invasive tool for predicting pathological grade of PDAC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 44 publications
(93 reference statements)
0
39
0
Order By: Relevance
“…IVIM is a noninvasive in vivo measurement which offers a quantitative technique to measure maternal placental perfusion and no contrast agent is used. Applications of IVIM were mainly in the liver, pancreas, kidney and prostate analysis currently [3][4][5][6][7][8]. Owing to the highly vascularized characteristic of the placenta with both a high blood fraction and a large perfusion component, it is also appropriate for evaluation with IVIM.…”
Section: Introductionmentioning
confidence: 99%
“…IVIM is a noninvasive in vivo measurement which offers a quantitative technique to measure maternal placental perfusion and no contrast agent is used. Applications of IVIM were mainly in the liver, pancreas, kidney and prostate analysis currently [3][4][5][6][7][8]. Owing to the highly vascularized characteristic of the placenta with both a high blood fraction and a large perfusion component, it is also appropriate for evaluation with IVIM.…”
Section: Introductionmentioning
confidence: 99%
“… 44 This approach allows separation of the diffusion and perfusion signal component of the water molecules, and could improve tissue characterisation such that tumours might be distinguished by pathological grade. 45 , 46 However, these existing DWI models lack specificity for various elements of the tissue microstructure, such as cell size, shape, intracellular structure, and perfusion effects. An improved framework for describing diffusion behaviour was proposed by Panagiotaki et al 47 This Vascular, Extracellular, and Restricted Diffusion for Cytometry in Tumours (VERDICT) method uses a three-compartment model to specifically account for intracellular, interstitial and intravascular water and map descriptors, which form key components of histopathological tumour assessment (Fig.…”
Section: Advances In Mrimentioning
confidence: 99%
“…As an alternate method for diagnosing acute pancreatitis, MR imaging (MRI) and MR cholangiopancreatography (MRCP) shows great potential in clinical applications (7). The benefits of MRI for acute pancreatitis are as follows: (I) the MRI sequence for T2-weighted image (T2WI) is highly sensitive to liquid and thus can visualize a small amount of liquid in mild pancreatitis, T2WI can characterize non-liquid materials in the pancreatic collections better than CT (6); (II) MRI clearly shows the areas of necrosis without enhancement and is safe for patients who are unable to receive iodinated contrast material because of allergies or kidney failure (8,9); (III) MRCP can noninvasively evaluate the changes of the bile ducts (especially the distal bile duct, which is difficult for ultrasound to show) and pancreatic duct system and help diagnose the etiology of the disease (10); (IV) recent studies have found that in addition to the air bubbles, high signals on the MRI diffusion-weighted imaging (DWI) sequences can also indicate the existence of infection to preliminarily determine whether the accumulation is infected (11); (V) novel MRI techniques such as intravoxel incoherent motion (IVIM) imaging can assess both perfusion and diffusion of the diseased tissues (12)(13)(14); (VI) MRI can be used to stage AP and clearly show local complications. It has been reported that non-enhanced MRI is more reliable and accurate than CT in estimating the severity of AP (9); and (VII) finally, MRI does not require ionizing radiation and does not lead to adverse effects on the human body.…”
Section: Introductionmentioning
confidence: 99%